2019
DOI: 10.1371/journal.pone.0209937
|View full text |Cite
|
Sign up to set email alerts
|

The complete genome sequence of an alphabaculovirus from Spodoptera exempta, an agricultural pest of major economic significance in Africa

Abstract: Spodoptera exempta nucleopolyhedrovirus (SpexNPV) is a viral pathogen of the African armyworm, Spodoptera exempta (Lepidoptera: Noctuidae), a significant agricultural pest of cereal crops in Africa. SpexNPV has been evaluated as a potential insecticide for control of this pest and has served as the subject of research on baculovirus pathology and transmission. Occlusion bodies (OBs) of SpexNPV isolate 244.1 were examined, and the nucleotide sequence of the genome was determined and characterized. SpexNPV-244.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 59 publications
0
1
0
1
Order By: Relevance
“…More recently, Redman et al [ 104 ] cloned an isolate of SpexNPV in vivo, identifying at least 17 genetically distinct genotypes, which varied in size from approximately 115 to 153 Kbp. Subsequently, Escasa et al [ 105 ] reported fully sequencing the genome of a SpexNPV isolate, collected in Tanzania in the 1970s, and thus very likely the same isolate as investigated by Redman et al [ 104 ]. The genome was 129.5 Kbp.…”
Section: Baculovirusesmentioning
confidence: 99%
“…More recently, Redman et al [ 104 ] cloned an isolate of SpexNPV in vivo, identifying at least 17 genetically distinct genotypes, which varied in size from approximately 115 to 153 Kbp. Subsequently, Escasa et al [ 105 ] reported fully sequencing the genome of a SpexNPV isolate, collected in Tanzania in the 1970s, and thus very likely the same isolate as investigated by Redman et al [ 104 ]. The genome was 129.5 Kbp.…”
Section: Baculovirusesmentioning
confidence: 99%
“…A partir del mapeo genómico de los genes correspondientes a estas proteínas estructurales, se observó una elevada sintenia en este grupo de genes de EpapGV y SfGV (Figuras 2.3 y 2.4). Más aún, en ambos granulovirus se confirmó la presencia de una región colineal densamente poblada con core genes estructurales (región colineal baculoviral), que ha sido descripta previamente en otras especies de baculovirus 133,134 y se postula como un elemento genómico conservado en los géneros Alphabaculovirus y Betabaculovirus. La comparación entre los proteomas de distintos miembros de la familia Baculoviridae evidenció que esta región, en comparación con el resto del genoma viral, se encuentra densamente ocupado por secuencias codificantes asociadas con funciones estructurales (Figuras 2.5).…”
Section: Componentes Estructurales Detectados En Los Ob De Epapgv Y Sfgvunclassified